Kodály yaklaşımına göre uygulanan armoni dersinin başarıya, tutuma ve performansa etkisi - Avşar, Mustafa (My University, 2018)
KODÁLY YAKLAŞIMINA GÖRE UYGULANAN ARMONİ DERSİNİN BAŞARIYA, TUTUMA VE PERFORMANSA ETKİSİBu araştırma, Kodály Yaklaşımı’na göre uygulanan Armoni dersinin başarı, tutum ve performans üzerindeki etkisini ortaya koymak amacıyla yapılmıştır. Öntest-sontest kontrol gruplu deneysel desenin kullanıldığı araştırmanın çalışma grubunu Armoni dersi alan toplam 40 ikinci sınıf lisans öğrenci oluşturmuştur. Grup dağılımına göre 20’si deney, 20’si kontrol; cinsiyet dağılımına göre 25’i kız, 15’i erkektir. Ölçme araçları her iki gruba da uygulanarak grupların denklikleri sağlanmıştır. Araştırmanın nicel verileri, araştırmacı tarafından geliştirilen 35 soruluk “Başarı Testi”, 15 soruluk “Gözlem Formu”, 10 soruluk “Duyum Testi” ve Eşlik Dersi Tutum Ölçeği’nden Armoni dersine uyarlanan “Tutum Ölçeği” ile, nitel verileri ise “Görüşme Formu” ile toplanmıştır. Verilerin çözümlenmesinde Wilcoxon testi, Mann Whitney-U testi ve frekans yüzde dağılımı yapılmıştır. Deney grubunda 28 haftalık güz ve bahar dönemi boyunca Armoni dersi Kodály Yaklaşımı’na göre işlenmiş, kontrol grubunda ise ders Geleneksel Öğretim ile sürdürülmüştür.Araştırma sonucunda;1. Kodály Yaklaşımı’na göre uygulanan Armoni dersinin işlendiği deney grubu öğrencileri ile Geleneksel Yöntem’e göre Armoni dersinin işlendiği kontrol grubu öğrencileri arasında, başarı ve performans boyutunda deney grubu lehinde anlamlı fark bulunmuştur.2. Kodály Yaklaşımı’na göre uygulanan Armoni dersinin işlendiği deney grubu öğrencilerinin öntest-sontest Başarı Testi, öntest-sontest toplam tutum puanları, öntest-sontest toplam gözlem puanları ve öntest-sontest Duyum Testi puanları arasında, sontest lehinde anlamlı fark bulunmuştur. 3. Deney ve kontrol grubu öğrencilerinin uygulamalar hakkındaki görüşlerinin incelenmesi sonucunda ise, “dersin katkısı ve kazanımları” temasına bağlı, gruplara göre en çok deney grubu öğrencilerinin olumlu görüş bildirdiği görülmüştür.

THE EFFECT OF THE HARMONY COURSE APPLIED IN ACCORDANCE WITH THE KODÁLY APPROACH ON SUCCESS, ATTITUDE AND PERFORMANCEThis research has been conducted on Harmony classes applied to Kodály Approach in order to reveal its influence over success, attitude and performance.The study group of the research, where pretest-posttest experimental design with a control group was used, consisted of 40 sophomore bachelor's students who take Harmony class. According to group distribution, 20 of them were included in the experiment group, 20 of them were in control group; according to gender distribution, 25 of them were women, 15 of them were men. Assessment instruments were utilized on both groups to ensure equivalency.Quantitative data of the research were 35-question “Success Test”, 15-question “Observation Form”, 10-question “Hearing Test” and “Attitude Scale” which was adapted for Harmony class from Accompaniment Class Attitude Scale, and the qualitative data were collected with “Interview Form”. Wilcoxon test, Mann Whitney-U test, and frequency percentage distribution were used for the analysis of the data. Harmony class which received training according to Kodály Approach was lectured during the 28-week fall and spring semester for the experiment group, and Conventional Instruction was maintained for the control group.In consequence of the research;1. A significant difference on the side of experiment group was found between the success and performances of experiment group where Harmony classes were applied according to Kodály Approach and control group where Harmony classes were lectured according to Conventional Method.2. A meaningful difference on the side of posttest was found among the scores of experiment group where Harmony classes were applied according to Kodály Approach for pretest-posttest Success Test, pretest-posttest total attitude scores, pretest-posttest total observation scores and pretest-posttest Hearing Test scores.3. It was seen that experiment group students mostly expressed a positive opinion regarding the “contribution and outcomes of the classes” theme between the two groups in the light of the analyses of the opinions of experiment and control group students about the practices.
Keywords: Armoni; Armoni Eğitimi; Criticism and interpretation; Eğtim ve öğretim; Eleştiri ve yorum; Harmony; Harmony Teaching; Instruction and study; Kodály Prensipleri; Kodály Yaklaşımı; Kodály Yöntemi; Kodály, Zoltán, 1882-1967; Koldáy Approach; Koldáy Method; Koldáy Principles; Musical Hearing Reading Writing; Müziksel İşitme Okuma Yazma; Okul müziği; School music